Internal Erosion in Earthdams, Dikes and Levees Proceedings of EWG‐IE 26th Annual Meeting 2018 - Bonelli, Stéphane; Jommi, Cristina; Sterpi, Donatella; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers the peer-reviewed contributions presented at the 26th Annual Meeting of the European Working Group on Internal Erosion in Embankment Dams, Levees and Dikes, and their Foundations (EWG-IE), held in Milano, Italy, on 10-13 September 2018. The meeting served as a fertile platform for discussion, sharing sound knowledge and introducing novel ideas on issues related to soil internal erosion in water retaining structures. The contributions encompass various aspects of laboratory techniques and findings, modelling and design criteria as well as prevention measures and field assessment. The book is a valuable, up-to-date tool that provides an essential overview of the subject for scientists and practitioners alike, and inspires further investigations and research.
Effects of suffusion on the soil's mechanical behavior: experimental investigations -- The role of seepage flow rate and deviatoric stress on the onset and progression of internal stability in a gap-graded soil -- Effects of void ratio and hydraulic gradient on permeability and suffusion of glacial till cores -- Reliability underseepage assessment of levees incorporating geomorphic features -- Simplified estimation of some main characteristics of pores and constrictions in granular materials -- Numerical and physical modelling of seepage-induced internal erosion around holes on permeable sheet pile -- Collection and analysis of the reactivation data of the historical sand boils in the Po river levees -- Harmonisation of terminology and definitions on soil deformation due to seepage.
Keywords: Engineering geology; Geotechnical engineering; Mechanics, Applied; Solids; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Solid Mechanics